Project-Based Learning Integrated with STEAM: A Study on Educational Pop-Up Books for Early Literacy - Chafidah, Nur; Hayati, Nur; Maryatun, Ika Budi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study evaluates the effectiveness of integrating Project-Based Learning (PjBL) with Science, Technology, Engineering, Arts, and Mathematics (STEAM) to enhance literacy skills among children aged 5-6. Employing a quasi-experimental design, 30 TK Cornerstone Homestyle Education students were selected and divided into experimental and control groups. The experimental group engaged in PjBL integrated with STEAM, while the control group followed conventional methods. Pre-tests and post-tests were administered to assess literacy skills, focusing on reading habits, symbol recognition, word writing, and constructing written pieces. Data were collected through tests and observation sheets and analyzed using descriptive and inferential statistics via IBM SPSS Statistics version 21. Results showed significant literacy skill improvements in the experimental group compared to the control group, with higher post-test scores and increased engagement. Instrument validity was confirmed through item analysis, and reliability was ensured with a Cronbach's Alpha of 0.74. Observations revealed high implementation quality in both groups, but the experimental group demonstrated a more substantial increase in literacy levels. This study concludes that STEAM-integrated PjBL effectively enhances early literacy, promotes creativity, and engages students actively in learning. The findings imply the need for broader application of this method in early childhood education and suggest further research to explore long-term impacts and applicability across diverse educational contexts. Despite limitations such as sample scope and short-term intervention, this research supports adopting interdisciplinary approaches for improved educational outcomes.